Duração do ciclo de vida de Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae: Leptysminae) e aspectos de seu comportamento alimentar na Amazônia central - Vieira, Maria de Fátima; Santos, Aldaléia Carmo dos (Acta Amazonica, 2003)
Life cycle of the grasshopper Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae: Leptysminae) is dependent on Eichhornia (Pontederiaceae). Experiments were carried outdoors during receding water, the Mating last for about 40 and 120 minutes. The ootheca has an average of 13.4 (+/- 3.2) eggs. Incubation lasted for 34.1 days (+/- 1.97). Mean durations of total development from egg to adult was 156.2 days, being 34.1 in the egg stage, 53.4 in the ninphal stage, and 68.7 in the adult stage. Nymphs (N) and adults (A) accepted only six aquatic macrophytes out of 13 species offered during 30 days; survived more time in Pistia stratiotes (N = 43 %, 30 days and A = 1 %, 27 days) and Pontederia sp. (N = 85 % and A = 40 % until 24 days) than Limnobium sp. (N =13% and A =10 % until 12 dias), Ludwigia sp. (N =3 %, 24 days and A =15 %, 9 days) Azolla sp. (N =35 %, 9 days and A =15 %, 12 days) and Paspalum repens (N =3 %, 21 days and A =5 %, 24 days).
Life cycle of Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae: Leptysminae) and aspects of its food behavior at Central Amazonia
Keywords: Life Cycle; Cornops Aquaticum; Aquatic Macrophytes; Amazon; Ciclo De Vida; Cornops Aquaticum; Macrófitas Aquáticas; Amazônia